APPLICATION OF HR-MARKETING TOOLS IN ASSESSMENT OF FACTORS OF QUALITY OF WORKING LIFE - ТELNOV, ANATOLIY; RESHMIDILOVA, SVITLANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of the article is to substantiate the tools of HR-marketing in assessing the factors of quality of working life.The article substantiates the need to use HR-marketing tools in assessing the factors of quality of working life at the enterprise. The quality of working life as a degree of satisfaction of personal needs and interests of employees through work in the enterprise, an indicator of well-being, free realization of intellectual and creative potential of the individual is the object of study of HR-marketing. The analysis of modern trends in the development of HR-processes is carried out. One of the areas of HR-marketing at the company is the periodic assessment of factors that shape the quality of working life. Its purpose is to identify factors that have a positive or negative impact on employee performance. According to the results of the survey of employees on satisfaction with various factors of quality of working life, those of them are identified that have a positive (negative) impact on employees and the results of their work. The results of the expert assessment showed the following hierarchy of factors of quality of working life: material incentives, favorable psychological climate in the team, training and professional development, provision of information and communication networks and digital technologies of the workplace, favorable working conditions, social security. An integrated indicator of satisfaction with the quality of working life indicates a fairly high level of employee satisfaction with factors of quality of working life. According to the results of the study, measures are proposed to improve the quality of working life and employee satisfaction with the social and labor sphere of the enterprise.
Keywords: staff; HR-marketing; HR-marketing approach; HR-specialist; HR-marketer; HR-brand; quality of working life; satisfy employees; work activity